Zagospodarowanie terenów zalewowych Warty w wybranych miastach - Jawgiel, Kamil; Łukaszewicz, Jan (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2016)
Floodplains are administered by the Regional Water Management Authority; the establishment of floodplains is justified only in exceptional cases. The main argument against such areas is heavy material losses and human security. These areas have been developed in a cartographic form on the hazard- and flood risk maps as part of the IT System of Protecting the Country from Extreme Hazards (ISOK). In large cities like Poznan, Gorzow Wielkopolski and Konin where the impact of human activity is particularly severe, floodplains are used in different ways. The cities in question try to make an effective use of the floodplains. The aim of the study is to present the structure of land use in selected cities located along the Warta and to identify potential material losses resulting from the flooding.
Keywords: Land use; Warta River; floodplains; GIS; flood